The Preparedness Analysis of of School Communities in Facing Flood Disaster. Case Study in 34’s Public Junior Highschool (SMPN 34) Bandar Lampung City - Zulkarnain; Listumbinang Halengkara (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2020)
The aim of this research is to describe the community preparedness in 34 Public Junior High School Bandar Lampung and to recommend some of mitigation efforts that can be done. This research use quantitative descriptive method. The populations in this research are the entire school community of 34 Public Junior High School Bandar Lampung, consisting of school administrators, teachers, and students. Data collected by questionnaires, observation, interview, and documentation. While Preparedness Index Formula from LIPI is used for data analysis. The results of this research indicate that the community preparedness in 34 Public Junior High School Bandar Lampung was categorized as “prepared” with the index value 72,17, while school community components consist of school as institutions (S1) was categorized as “Prepared” with index value of 73,35, teacher (S2) was categorized as “prepared” with index value of 72,87, and student (S3) was categorized as “prepared” with index value of 65,75. However mitigation effort can used active (structural) and pasive (non-structural).